EFFECTIVENESS OF REHABILITATION OF DRUG DEPENDENT CLIENTS AT THE PINTU HIJRAH FOUNDATION BANDA ACEH - Hijrah Saputra; Teuku Radja Furqan (Adisam Publisher, 2024)
Rehabilitation is one of the government's efforts to handle abuse of narcotics, that the implementation of rehabilitation in efforts to handle narcotics abuse can be done in two ways, namely social rehabilitation which is an integrated process of recovery activities, both physical, mental, and social. Drug abuse is a case that is increasing day by day increasing, both in terms of quantity and quality. It is which cannot be taken lightly because most cases of drug abuse it is found in young people, the next generation of the nation. Hijrah Door Foundation is one of the social rehabilitation places in Banda Aceh with using Islamic therapy. Clients who were rehabilitated there came from various Districts/Cities in Aceh and now it has returned to families and communities. This study aims to analyze the effectiveness of the rehabilitation of drug dependent clients at the Pintu Hijrah Banda Foundation aceh. This research is a qualitative descriptive research. Data obtained by observation, interviews and documentation. The results of the research are the implementation of these 12 steps carried out for 6 months has been effective because of the programs provided during rehabilitation, the targets were set, the satisfaction was high given to make the client live a normal life and be accepted back inside society and no longer tempted to consume drugs. It also makes The Pintu Hijrah Foundation is a recommendation for drug rehabilitation in Aceh.